ANALISIS TERHADAP PENETAPAN PENGADILAN AGAMA JAKARTA BARAT NO. 28/PDT.P/2017/PA.JB DALAM PENETAPAN DISPENSASI PERKAWINAN ANAK DI BAWAH UMUR DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DAN KOMPILASI HUKUM ISLAM (STUDI KASUS PERKAWINAN ANAK ANTARA MUHAMAD LUKMAN DAN LINA YULIANTI) - Sabrina Agatha Faustina; Mulati . (Fakultas Hukum Universitas Tarumanagara, 2018)
The aim of a marriage according to the Law Number 1 year 1974 is an effort to build a happy and everlasting family based upon the Divinity of Almighty God. The law Number 1 year 1974 contains a principle which explains that both candidates for husband and wife should have already mature in physical and biological, in order to have a good and everlasting marriage without end up in divorce and to obtain a good and healthy offspring thereof. Paragraph 7 Article 1 of the law Number 1 year 1974 stipulated that a man had a right to get marriage if he has been 19 year old and for woman if she has been 16 year old. Even though this time limit of the age herein had been stipulated briefly and clearly, but in the fact it happen frequently that there are still many underage marriage to take place. The court could give a permit to get married and a marriage age dispensation herein through a court decision if he/she had fulfilled a prerequisite procedure and requirement as well. In this point, judge is the main determinant in giving the dispensations.